2019
DOI: 10.1002/cam4.2372
|View full text |Cite
|
Sign up to set email alerts
|

Increased lymph node yield indicates improved survival in locally advanced rectal cancer treated with neoadjuvant chemoradiotherapy

Abstract: Purpose It is recommended for colorectal cancer to harvest at least 12 lymph nodes (LNs) during surgery to avoid understaging of the disease. However, it is still controversial whether it is necessary to harvest from locally advanced rectal cancer (LARC) patients who underwent neoadjuvant chemoradiotherapy (neo‐CRT). The impact of lymph node yield (LNY) on prognosis in LARC patients was analyzed. Materials/Methods In total, 495 LARC patients who underwent neo‐CRT in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…In our multivariate analysis, the number of harvested lymph nodes was one of the independent predictors of PFS. This finding was consistent with previous studies by Xu et al [28] and Wang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…In our multivariate analysis, the number of harvested lymph nodes was one of the independent predictors of PFS. This finding was consistent with previous studies by Xu et al [28] and Wang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…In our multivariate analysis, the number of harvested lymph nodes was one of the independent predictors of PFS. This nding was consistent with previous studies by Xu et al [28] and Wang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, some of the findings also noted that retrieval of less than 12 lymph nodes in the proctectomy specimen of rectal cancer treated with NAT had no adverse effect on long-term survival and may be a marker of higher tumor response [26][27][28][29]. On the contrary, other studies indicated that lymph node yield was an independent predictor of survival in rectal cancer irrespective of NAT [30,31]. In our matched cohort, propensity score matching basically eliminated the difference in NAT between LRC and M/HRC patients.…”
Section: Discussionmentioning
confidence: 98%